The Collegial Tradition in the Age of Mass Higher Education - Tapper, Ted.; Palfreyman, David; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2010)
This book will examine the relationship between collegiality and the collegial tradition in the context of the development of mass higher education. The collegial tradition in higher education has been shaped above all by the collegiate universities. In all its various forms (as commensality, as a mode of governance, and as a critical force in shaping the process of teaching, learning and research) the collegial tradition has found sustenance in many sectors of higher education. It may well be that the tradition as expressed in these forms now has more strength and depth in the non-collegiate than in the collegiate universities. This work will give a fuller picture of the present-day character of British (especially English) higher education. Although this is a book that will rely particularly upon the Oxford experience of collegiality, there will be extensive comparative and international reference to the idea of collegiality, the various challenges to it that have emerged within different national systems, and the contrasting patterns of adjustment to those challenges.
Collegiality: Definitions and Challenges -- Collegiality: Setting the Agenda -- The Collegial Tradition in Higher Education -- Collegiality: The Contemporary Challenges -- Collegiality in Action -- Collegiality as Colleges -- The Slippery Slope Known as Federalism -- Managerialism as Collegiality: The Impossible Conjuring Trick? -- Cross-National Perspectives on Collegiality -- Lessons from America: A Comparative Perspective on the Collegial Tradition -- Lessons from Continental Europe: The Collegial Tradition as Academic Power -- Whither Collegiality? -- Collegiality Revisited: Continuity, Rejuvenation or Demise?.
Keywords: Education; Education, Higher; Education; Educational Policy and Politics; Higher Education; Sociology of Education